Diversity and guild structure of insects during rice flowering stage at a selected rice field in Penang, Malaysia - Nur Aida Hashim,; Masniza Abd Aziz,; Norasmah Basari,; Khadijah Saad,; Aiman Hanis Jasmi,; Suhaila Ab Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2017)
A study on diversity of insects in rice field was conducted at Kg Terus, Guar Perahu in Penang. This study aims to determine the diurnality and guild structure of insect in rice field specifically during the flowering stage of rice. Insects were collected using sweep net method and light trap method. Overall, a total of 1936 insect specimens representing 28 species, 19 families and seven orders were collected. Twenty five species from 19 families were caught during day time while 17 species from 13 families were trapped at night. Coleopterans were the dominant insect captured during day time sampling with Micraspis crocea from family Coccinellidae captured in highest number (223). In contrast, Hemipterans was dominant during night time with Nilaparvata lugens from family Delphacidae found in highest number (258). The Odonata recorded the highest diversity index (H’= 1.2587) while Coleoptera recorded the highest richness index (Imargalef = 5.8390) values for diurnal insect. For nocturnal insect, Hemiptera recorded the highest values for both diversity index (H’= 1.2655) and richness index (Imargalef = 5.8390). In term of guild structure, the rice pest was the most dominant insect found in rice field for both diurnal and nocturnal group. This followed by predator, others (visitor/pollinator) and parasitoid groups. Result of this study will identify the classification of insect present during the flowering stage of rice allowing farmers to forecast pest population build up to assist in the pesticides selection that will be generally applied at the end of flowering stage. This consequently will help to conserve beneficial insects and lower the pest management cost.